Grandfather's journey - Say, Allen; Juvenile Collection (Library of Congress) (Boston : Houghton Mifflin, 1993)
A Japanese American man recounts his grandfather's journey to America which he later also undertakes, and the feelings of being torn by a love for two different countries.
Source: Copyright deposit, Dec. 21, 1993.
Keywords: Grandfathers -- Fiction; Voyages and travels -- Fiction; Homesickness -- Fiction; Japanese Americans -- Fiction; Caldecott Medal; Japan -- Fiction; United States -- Description and travel -- Fiction; Imprints 20th century 1993